2018
DOI: 10.3390/jof4010038
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Burden of Serious Human Fungal Infections in Malaysia

Abstract: Fungal infections (mycoses) are likely to occur more frequently as ever-increasingly sophisticated healthcare systems create greater risk factors. There is a paucity of systematic data on the incidence and prevalence of human fungal infections in Malaysia. We conducted a comprehensive study to estimate the burden of serious fungal infections in Malaysia. Our study showed that recurrent vaginal candidiasis (>4 episodes/year) was the most common of all cases with a diagnosis of candidiasis (n = 501,138). Oesopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…Based on the assumption that 22.3% of microbial keratitis are due to fungi, we estimated the incidence of fungal keratitis in Turkey at 33 per 100 000 population annually, which suggests fungal keratitis is a particular problem in Turkey. This estimate is more than expected number of cases in Italy (0.94/100 000), Malaysia (1.3/100 000) and Egypt (14/100 000) and less than Pakistan (44/100 000) and Nepal (73/100 000) …”
Section: Resultsmentioning
confidence: 99%
“…Based on the assumption that 22.3% of microbial keratitis are due to fungi, we estimated the incidence of fungal keratitis in Turkey at 33 per 100 000 population annually, which suggests fungal keratitis is a particular problem in Turkey. This estimate is more than expected number of cases in Italy (0.94/100 000), Malaysia (1.3/100 000) and Egypt (14/100 000) and less than Pakistan (44/100 000) and Nepal (73/100 000) …”
Section: Resultsmentioning
confidence: 99%
“…Because of these studies, which are lacking in other South East Asian countries, higher numbers of cases reported in Thailand and Malaysia may in part be due to increased levels of clinical awareness rather than an actual increased prevalence of the disease in those places. In Thailand and Malaysia, the HIV-associated burden of histoplasmosis has been calculated at 184 and 175 for Thailand [44] and Malaysia [45] respectively, indicative of major under-reporting of cases. These studies demonstrated the potentially high mortality of histoplasmosis in AIDS; for example Wongprommek reported a survival rate at 6- and 12-month of 88% and 75%, respectively, out of 57 cases, not all HIV positive [42].…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies reporting the nationwide burden of candidemia in Asia. In Malaysia and Vietnam, it was estimated to be five per 100,000 population, without any direct data to support these estimates [12,13].…”
Section: Discussionmentioning
confidence: 99%